Two dimensional semiconducting transition metal dichalcogenides via thermally assisted conversion - synthesis, characterisation and electronic properties - GATENSBY, RILEY JOHN (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
2D transitional metal dichalcogenides (TMDs) are of major interest to the research and electrical engineering community. A number of TMDs are semiconducting and have a wide range of bandgaps, they can exhibit n- or p- type behaviour, and the electronic structure changes with the number of layers. These interesting properties hold much promise for a host of electrical applications including low or high power field effect transistors, sensors and diodes. Moreover the unique optical properties and direct bandgap of monolayer TMDs make them attractive for optoelectronic applications such as Light Emitting Diodes (LEDs), photodiodes, couplers and photovoltaic cells. Many reports of 2D TMDs electrical properties involve devices created by micromechanical exfoliation. While providing pristine material, this method is laborious and is not suitable for anything larger than lab-scale demonstrations. In order to fulfil the potential of these materials, a synthesis route which is well controlled, scalable, and reproducible is required. A further prerequisite is the ability of the materials to be integrated with semiconductor industry process flows. Thermally assisted conversion (TAC), a variant of chemical vapour deposition (CVD), shows much promise for meeting these requirements. This thesis provides a detailed treatise on the development and subsequent characterisation of 2D TMDs produced from TAC. The TAC process produces thin films of polycrystalline TMDs. In order to synthesise and investigate these materials, a Low Pressure Chemical Vapour Deposition (LPCVD) system was designed and built in house. Firstly sulfide based TMDs are considered, particularly MoS2 and WS2. Due to well-regulated metal deposition conditions, TAC was shown to be suitable for producing continuous MoS2 thin films from bulk like thicknesses (≥ 20 nm) down to films with monolayer character. This is notable because monolayer MoS2 is a direct bandgap material, and thus optoelectronic applications come within the remit of this scalable synthesis method. Films were characterised by a suite of methods including scanning Raman spectroscopy, X-ray Photoelectron Spectroscopy (XPS) and electron microscopy. Electronic devices fabricated from MoS2 include Hall bars, Thin Film Transistors (TFTs) and chemiresistor gas sensors; these probed the electrical quality of the TAC materials. Unencapsulated devices exhibited room temperature Hall mobilities of 0.5-1 cm2V-1s-1. These values are too low for logic applications, however they compare well to literature values for MoS2films synthesised in an industrially relevant manner. Electrical Double Layer (EDL)-TFTs showed mobilities of 1.4 cm2V-1s-1 and this was increased to 10 cm2V-1s-1 when the synthesis temperature was increased to 1000 ?C. Chemiresistor gas sensors are a very suitable application for 2D TMDs due to their high surface area to volume ratio. Sensors were created featuring low power room temperature operation, fast response times and ultra-high sensitivity. MoS2sensors demonstrated an empirical limit of detection (LOD) of 300 ppb, and a theoretical LOD of 51 ppb for NH3. TAC growth was then extended to include the corresponding selenides. Another LPCVD system was designed and built, affording the opportunity to include automation and data-logging capabilities. Selenide thin film synthesis recipes for MoSe2 and WSe2 were developed and optimised. Temperature was shown to be a critical parameter in film growth. The films were characterised using the same techniques as were used for the sulfides. Electrical characterisation of the selenide family of TMDs showed generally better performance than the sulfides. EDL-TFTs made from MoSe2synthesised at 800 ?C showed a mobility of 4.3 cm2V-1s-1, this increased to 20.6 cm2V-1s-1 for samples grown at 1000 ?C. Chemiresistor sensors from selenides were also very sensitive. Devices utilising MoSe2 exhibited a LOD of 0.8 ppm for NO2and 2 ppm for NH3. WSe2 sensors displayed a LOD of 0.8 ppm to NH3. The TAC process is a viable method to produce 2D TMDs in an industrially relevant manner. It produces high quality thin films and it is potentially applicable for synthesising many different TMDs. The electronic quality of the material produced is such that logic applications are limited. However, there are a host of areas where TAC holds much promise, including sensing, catalysis and optoelectronics.
APPROVED
Keywords: nanoscience; transition metal dichalcogenide; semiconducting; materials